(untitled) (Journal of Environmental Bioremediation and Toxicology, 2013)
A diesel-degrading bacterium has been isolated from a primary school soil. The isolate was tentatively identified as Serratia sp. Strain DRY5 based on the carbon utilization profiles using Biolog GN plates and partial 16S rDNA molecular phylogeny. Isolate 5 showed an increase cellular growth with respect to diesel concentrations from 0% until 2% where the optimum growth occurring at 2% (v/v) diesel concentration and was able to tolerate up to 8% (v/v) diesel. Based on the optimization studies using different nitrogen sources, Ammonium chloride proved to be the best nitrogen source. Ammonium chloride was optimum at 7.7 gl-1 and concentrations higher than that resulted with inhibiton of the cellular growth. The optimal temperature and the optimal pH that supported the growth of this bacterium was between 23 to 40 oC and pH 7.5 to pH 8.5 respectively. Diesel components was proven to be completely removed from the reduction in the hydrocarbon peaks monitored by Solid Phase Microextraction Gas Chromatography analysis after 7 days of incubation.All of these characteristics suggest that this bacterium is the right bacterium for bioremediation of diesel spills and pollution in the tropics.